Folate Reverses NF-κB p65/Rela/IL-6 Level Induced by Hyperhomocysteinemia in Spontaneously Hypertensive Rats - Lihua Zhang; Lihua Zhang; Zhongliang Li; Changcheng Xing; Ning Gao; Rui Xu; Rui Xu (Frontiers Media S.A., 2021)
Hyperhomocysteinemia (HHcy) is derived from the abnormal metabolism of homocysteine (Hcy) and is related to metabolic-related diseases. In addition, HHcy combined with hypertension increases the risk of cardiovascular diseases (CVD). However, the mechanism of HHcy aggravating hypertensive arterial damage and the efficacy of folate (FA) as a beneficial supplement have not been fully elucidated. In this study, we established a rat HHcy model and a hypertension combined with HHcy model. Rat tail artery blood pressure (BP), plasma Hcy, serum superoxide dismutase (SOD), and malondialdehyde (MDA) were measured. Rat thoracic aorta was for pathological analysis after 12 weeks of the experiment. The relative expression levels of oxidative stress and immune/inflammation in rat arterial tissues were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting. The results demonstrated that the relative expression levels of oxidative stress and immune/inflammation were the highest in the hypertension combined with HHcy group, followed by the hypertension group. Compared with the hypertension group, the hypertension combined with HHcy group up-regulated the expression levels of interleukin-6 (IL-6) and nuclear factor-κ-gene binding (NF-κB) p65/Rela, but not NADPH oxidase (Nox). Furthermore, folate inhibited the expression of IL-6 and NF-κB p65/Rela, reduced the levels of MDA and HHcy, but significantly increased the SOD level. In conclusion, HHcy synergistically aggravated the arterial damage factor of hypertension through immune/inflammatory response. However, folate demonstrated anti-inflammatory properties and reversed the NF-κB p65/Rela/IL-6 level induced by HHcy in hypertensive rats.